2013
DOI: 10.1103/physrevlett.110.077003
|View full text |Cite
|
Sign up to set email alerts
|

First-Order Superconducting Transition ofSr2RuO4

Abstract: By means of the magnetocaloric effect, we examine the nature of the superconducting-normal (S-N) transition of Sr(2)RuO(4), a most promising candidate for a spin-triplet superconductor. We provide thermodynamic evidence that the S-N transition of this oxide is of first order below approximately 0.8 K and only for magnetic field directions very close to the conducting plane, in clear contrast to the ordinary type-II superconductors exhibiting second-order S-N transitions. The entropy release across the transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
123
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 118 publications
(140 citation statements)
references
References 38 publications
(56 reference statements)
16
123
1
Order By: Relevance
“…Notice that this is worse than those achieved for more anisotropic superconductors such as Sr 2 RuO 4 (ref. 26), because of the relatively small out-of-plane H c2 anisotropy of Cu x Bi 2 Se 3 (see Supplementary Note 11). Nevertheless, this small anisotropy of Cu x Bi 2 Se 3 in turn makes the misalignment effect rather small, as explained in Supplementary Note 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notice that this is worse than those achieved for more anisotropic superconductors such as Sr 2 RuO 4 (ref. 26), because of the relatively small out-of-plane H c2 anisotropy of Cu x Bi 2 Se 3 (see Supplementary Note 11). Nevertheless, this small anisotropy of Cu x Bi 2 Se 3 in turn makes the misalignment effect rather small, as explained in Supplementary Note 3.…”
Section: Methodsmentioning
confidence: 99%
“…We used a 3 He- 4 He dilution refrigerator (Kelvinox 25, Oxford Instruments) to cool down the samples. We performed specific-heat measurement in the temperature range 0.09 K ≤ T ≤ 4 K. We constructed a custom-made high-resolution calorimeter 26 , shown in Supplementary Fig. 1a.…”
Section: Methodsmentioning
confidence: 99%
“…The discrepancies in the orientation of the d-vector are even aggravated by the extreme sensitivity of the H c2,ab suppression [13] as well as by the in-plane anisotropy of H c2,ab (φ) [19,20] to the precise field alignment. Although introducing a multi-component order parameter seems rather unconvincing that it might apply to all cases [21,22], it might be relevant to the chiralnonchiral transition in vortex states [23,24] or even to the first-order transition to the normal state [14]. Further complicating matters, one set of scanning tunneling microscopy (STM) experiments was consistent with a single nodeless gap on all three Fermi surfaces of Sr 2 RuO 4 [25], but in another STM experiment, the tip was placed in a spot with substantial normal regions for T ≪ T c [26], completely disguising any possible superconducting order parameter form.…”
Section: Introductionmentioning
confidence: 99%
“…Under an in-plane magnetic field, the possibility of SC double transitions has been reported. [12][13][14][15][16][17] However, recent thermal measurements 18,19 revealing the first-order SC transition without a clear second anomaly have suggested that the previously reported anomalies may have originated from the broadening of the first-order transition or from sample mosaicity. Thus, the existence of double transitions in the in-plane magnetic field is still unclear.…”
Section: Introductionmentioning
confidence: 98%